Auto Racking System Prototype For Forklift Replacement Industrial Goods Distribution - Sylvestre Maniriho (Universitas Nusa Putra, 2019)
Automation is one of the technological developments and is an alternative to obtaining a working system that is more practical, efficient and has a low accident rate to get a high level of accuracy as well. The process of transporting and packing goods can be done by using tools to make it easier and lighten the work of humans. At this time, PLC has played an essential role in the industrial world, various applications have been developed using a PLC control system, so it is critical for us electrical engineering students to learn and understand PLC as a provision for us when we enter the industrial world. Therefore Automation This racking system can be a learning tool for electrical engineering students, especially in the PLC field. The results of research and discussion have been stated. The use of limit switches is essential in this system. To determine which motor will be active and which engine will be off. And as a determinant of the direction of the pallet will be brought. With HMI, you can monitor which components are active and count the number of pallets that go in and out. The system has been able to run properly and correctly even though the mechanical problem is not yet perfect. Before making a miniature, we must prepare the concept in advance, so it is easy to design. Understand the process and workings of the tools we make. Understand the specifications of the components that we will use.